2020
DOI: 10.3389/fonc.2020.01212
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Incidence and Survival of Gastric Cancer Based on the Lauren Classification: A Large Population-Based Study Using SEER

Abstract: Background: Limited evidence exists on the incidence of gastric cancer (GC), and contradictory results exist for the prognosis of GC based on the Lauren classification. We analyzed the incidence and survival of GC based on the Lauren classification. Methods: The Surveillance, Epidemiology, and End Results (SEER) database from 1975 through 2015 was used to identify all patients with surgically resected, histologically diagnosed intestinal or diffused-type GC. Propensity score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Intestinal-type gastric adenocarcinoma includes carcinoma [not otherwise specified (NOS); M8010], adenocarcinoma (NOS; M8140), tubular (M8211), and intestinal-type (M8144). Meanwhile, the diffuse type includes SRC (M8490), diffuse carcinoma (M8145), and linitis plastica (M8142) (23).…”
Section: Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Intestinal-type gastric adenocarcinoma includes carcinoma [not otherwise specified (NOS); M8010], adenocarcinoma (NOS; M8140), tubular (M8211), and intestinal-type (M8144). Meanwhile, the diffuse type includes SRC (M8490), diffuse carcinoma (M8145), and linitis plastica (M8142) (23).…”
Section: Patientsmentioning
confidence: 99%
“…The first study by Tang et al revealed that diffuse-type early gastric cancer (EGC) had a better prognosis than intestinal-type EGC by using PSM for adjusting confounders. However, after matching, only 2,672 cases were included in their study, which might weaken the whole sample's representativeness (23). Herein, we performed multivariate regression first and then conducted PSM, and established a competing risk model to perform sensitivity analysis.…”
Section: A B C D E Fmentioning
confidence: 99%
“…Diffuse-type GC is more likely in women and younger patients and has a lower 5-year survival rate (10)(11)(12). Mix-type has the highest degree of malignancy due to variable biological behavior (13).…”
Section: Introductionmentioning
confidence: 99%
“…All the pathological types were adenocarcinoma, with 7 cases of liver metastasis and 4 cases of peritoneal metastasis. According to lauren classification (Tang et al, 2020) , 5 cases were classified as diffuse-type and 18 other types. Of these patients, 12 had undergone radical surgery, 4…”
Section: Results Characteristics Of Patients and Sequencing Datamentioning
confidence: 99%